Archiwa prywatne rodzin szlacheckich z pogranicza Podlasia, Litwy i Lubelszczyzny w XVIII–XIX w. (w świetle Zbioru Zygmunta Glogera w Archiwum Państwowym na Wawelu) - Ujma, Magdalena (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2017)
The primary source of knowledge in the subject careers are documents and files stored in the archives of the once private. Their pieces are among others in the ECR Zygmunt Gloger. Its advantage is a large variety. We find in the genealogical material and economic, excerpts from books municipal and earthly, worldly goods inventories, inventories of movable property, correspondence, and sources resulting from the functioning of the judiciary. Here are excerpts private archives rich in genealogical material and economic. The chronological range of content „Compendium Zygmunt Gloger” includes the era of traditional Polish as well as centuries XIX and XX (l. 1515–1907). Geographically it concerns among other things, Lithuania, Podlasie and Lublin province. An important part of the „Collection of Zygmunt Gloger” are records of family and property. The sources of this type generally includes correspondence, accounts, wills, documents or their copies proving ownership, extracts from court records, genealogical material. In the ECR Zygmunt Gloger stand out documents and files related to history: Branickich, Barzów, Biedrzychowskich, Potocki, Bielski, Woynów, Suchodolski, Poniatowski, Zamoyski, Czartoryski, Szembeków, Sapieha, the Radziwill, Denhoff, Lubomirski.